Production of G protein‐coupled receptors in an insect‐based cell‐free system. Issue 10 (3rd July 2017) - Sonnabend, Andrei; Spahn, Viola; Stech, Marlitt; Zemella, Anne; Stein, Christoph; Kubick, Stefan
ABSTRACT: The biochemical analysis of human cell membrane proteins remains a challenging task due to the difficulties in producing sufficient quantities of functional protein. G protein‐coupled receptors (GPCRs) represent a main class of membrane proteins and drug targets, which are responsible for a huge number of signaling processes regulating various physiological functions in living cells. To circumvent the current bottlenecks in GPCR studies, we propose the synthesis of GPCRs in eukaryotic cell‐free systems based on extracts generated from insect ( Sf 21) cells. Insect cell lysates harbor the fully active translational and translocational machinery allowing posttranslational modifications, such as glycosylation and phosphorylation of de novo synthesized proteins. Here, we demonstrate the production of several GPCRs in a eukaryotic cell‐free system, performed within a short time and in a cost‐effective manner. We were able to synthesize a variety of GPCRs ranging from 40 to 133 kDa in an insect‐based cell‐free system. Moreover, we have chosen the μ opioid receptor (MOR) as a model protein to analyze the ligand binding affinities of cell‐free synthesized MOR in comparison to MOR expressed in a human cell line by "one‐point" radioligand binding experiments. Biotechnol. Bioeng. 2017;114: 2328–2338. © 2017 The Authors. Biotechnology and Bioengineering Published by Wiley Periodicals, Inc. Abstract : Cell‐free protein synthesis based on a eukaryotic cell lysate as alternative production system for G protein‐coupled receptors (GPCRs) is described. The paper of Sonnabend et al. includes the successful synthesis of a variety of GPCRs ranging from 40 to 133 kDa. In addition the ligand binding affinities of cell‐free synthesized µ‐opioid receptor (MOR) in comparison to MOR expressed in a human cell line is characterized.